2007
DOI: 10.1007/bf03403709
|View full text |Cite
|
Sign up to set email alerts
|

Providing for the Sexual Health Needs of Canadian Immigrants

Abstract: Background: Sexual health is increasingly understood as an integral part of health. In Canada, education for sexual health is delivered predominantly in middle and secondary school. What of adults who immigrate to Canada from countries where sex education is not delivered to youth? This paper explores the needs and experiences of one such group of Canadian immigrants: those from Iran.Method: Ten married male and 10 married female immigrants from Iran living in a midsized Canadian city were recruited using snow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 13 publications
1
24
0
Order By: Relevance
“…In Canada, Asian immigrants have significantly lower rates than Canadian‐born women and other immigrant groups, even after many years of residence (McDonald and Kennedy 2007). These demographic differences may be associated with more barriers among Asian immigrants to Canada due to lack of knowledge of health‐related issues and the health care system, cultural attitudes and beliefs, gender roles, or lack of culturally appropriate services (Lai and Chau 2007; Maticka‐Tyndale, Shirpak, and Chinichian 2007; Wang 2007; Brotto et al 2008; Roth and Kobayashi 2008; Wang, Rosenberg, and Lo 2008). Given that the survey was not conducted in Asian languages, immigrants from Asian countries (especially newer immigrants with limited English proficiency) may have been underrepresented in the JCUSH data; thus, the low Pap test rates in Canada may in fact overestimate the true rates, which may be even lower.…”
Section: Discussionmentioning
confidence: 99%
“…In Canada, Asian immigrants have significantly lower rates than Canadian‐born women and other immigrant groups, even after many years of residence (McDonald and Kennedy 2007). These demographic differences may be associated with more barriers among Asian immigrants to Canada due to lack of knowledge of health‐related issues and the health care system, cultural attitudes and beliefs, gender roles, or lack of culturally appropriate services (Lai and Chau 2007; Maticka‐Tyndale, Shirpak, and Chinichian 2007; Wang 2007; Brotto et al 2008; Roth and Kobayashi 2008; Wang, Rosenberg, and Lo 2008). Given that the survey was not conducted in Asian languages, immigrants from Asian countries (especially newer immigrants with limited English proficiency) may have been underrepresented in the JCUSH data; thus, the low Pap test rates in Canada may in fact overestimate the true rates, which may be even lower.…”
Section: Discussionmentioning
confidence: 99%
“…The results of 59 published papers were synthesised. Thirty-eight studies were cross-sectional surveys , nineteen were qualitative studies [72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87][88][89][90], and two employed mixed methods design [91,92]. Table 1 shows The majority of studies were conducted in Iran and Turkey, which are the fastest growing medical research output in the Middle East [93].…”
Section: Study Design and Sample Characteristicsmentioning
confidence: 99%
“…Insufficient knowledge about contraception and lack of basic reproductive knowledge was reported as one of the main barriers to contraception use among Muslim women [20,26,29,31,39,41,46,83,90,91]. Some women are unaware of services available for them [69,74,75,78,87], particularly unmarried women [74,75,78].…”
Section: Theme 1: Insufficient Knowledge and Misconceptions About Conmentioning
confidence: 99%
“…Migrants and people belonging to culturally and linguistically diverse (CALD) background groups are often at risk of poor health outcomes, especially in relation to sexual health . For example in the UK, people from the Indian subcontinent were significantly different from people of English origin in terms of their sexual behaviour and contraceptive use …”
Section: Demographic Characteristics Reasons For Attendance Main DImentioning
confidence: 99%
“…These observations may also apply to other CALD communities in Australia and other countries with large migrant communities. For example, with regards to sexual health, a study conducted in adult Iranian migrants in Canada concluded that more attention needed to be paid to developing public health and medical services related to sexual health that took account of the cultural diversities in the population . CALD communities could thus potentially benefit from evidenced‐based, culturally and linguistically appropriate interventions and targeted health promotion.…”
Section: Demographic Characteristics Reasons For Attendance Main DImentioning
confidence: 99%